2022
DOI: 10.1155/2022/9052246
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perioperative Multimodal Pain Management on Postoperative Outcomes in Patients (Aged 75 and Older) Undergoing Short-Segment Lumbar Fusion Surgery

Abstract: Background. Due to the presence of multimorbidity and polypharmacy, patients aged 75 and older are at a higher risk for postoperative adverse events after lumbar fusion surgery. More effective enhanced recovery pathway is needed for these patients. Pain control is a crucial part of perioperative management. The objective of this study is to determine the impact of multimodal pain management on pain control, opioid consumption, and other outcomes. Methods. This is a retrospective review of a prospective collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…With our knowledge of the dangers of opioid prescriptions, the focus, as providers, needs to be on reducing opioid prescriptions while maintaining adequate postoperative pain control with a multimodal approach. 27 A recent study by Gottschalk et al found that a postoperative methylprednisone taper significantly reduces pain and opioid consumption after DRF surgery. 28 Many studies have focused nonmedication methods of pain management and emphasized the importance of preoperative education on pain control management and appropriate use of analgesia, finding that it is correlated with fewer readmissions and better follow-up, well-being, and pain indices.…”
Section: Discussionmentioning
confidence: 98%
“…With our knowledge of the dangers of opioid prescriptions, the focus, as providers, needs to be on reducing opioid prescriptions while maintaining adequate postoperative pain control with a multimodal approach. 27 A recent study by Gottschalk et al found that a postoperative methylprednisone taper significantly reduces pain and opioid consumption after DRF surgery. 28 Many studies have focused nonmedication methods of pain management and emphasized the importance of preoperative education on pain control management and appropriate use of analgesia, finding that it is correlated with fewer readmissions and better follow-up, well-being, and pain indices.…”
Section: Discussionmentioning
confidence: 98%
“…[20][21][22] In contrast, adequate pain management has been shown to facilitate postoperative mobilisation, improve mobility and promote better functional recovery. [23][24][25][26] Early mobilisation has been associated with reducing postoperative complications, including pneumonia, venous thromboembolism, pressure ulcers and delirium. [27][28][29] Therefore, optimal perioperative analgesia can facilitate elderly patients' perioperative recovery.…”
Section: Open Accessmentioning
confidence: 99%